Biomechanical performance of Ti-PEEK dental implants in bone: An in-silico analysis. (October 2022) - Ouldyerou, Abdelhak; Merdji, Ali; Aminallah, Laid; Roy, Sandipan; Mehboob, Hassan; Özcan, Mutlu
Abstract: Stress-shielding is caused by a significant mismatch in stiffness between bone tissue and Ti alloy dental implants. Therefore, in this study, a Ti-PEEK composite implant was examined and compared with conventional titanium, to determine the behavior of the host bone. Twelve 3D finite element models were modeled with two conditions of marginal cortical bone (with and without marginal bone loss). Six implant designs were constructed. Implant (A) was made with a conventional design (dense titanium), implants (B), (C) and (D) are designed with Ti-PEEK composite (outer layer made of PEEK and inner structures made of Ti with hexagonal, cylindrical, and cross shapes for implants (B), (C) and (D), respectively), the implant (E) is designed with Ti at the upper half section and PEEK at the bottom half section, and the implant (F) is designed with PEEK at the upper half section and Ti at the bottom half section. An axial load of 200 N was applied to the buccal cusp and central fossa of the occlusal surface. The displacements, stress, and equivalent strain were analyzed at the level of bone tissue. The mechanostat of Frost was used to determine the behavior of the cancellous bone under these biomechanical conditions. Results showed that strains were greater in cancellous bone with marginal bone loss than in healthy bone (w/o MBL). When compared to implants (B)-(F), conventional implant (A) did not produce as much strain. Thus, results and analyses suggest that the Ti-PEEK implants outperform compared with the implant (A) in the case of no marginal bone loss. However, the implants (A) and (E) perform equally in terms of bone loss.